Venezuelan-Bolivian Relations Between Decline and Development (Chavez and Maduro Era) - Hassan, Lecturer Dr. Hanan Faleh (The International and Political Journal, 2023)
This research deals with a historical overview of the relations between Venezuela and Bolivia. These relations began at the end of the nineteenth century, but they were on a limited scale and did not develop due to the internal circumstances of both countries. At the beginning of the rule of Venezuelan President Hugo Chavez, there was a clear development in relations between the two countries, especially during the period between 2006 and 2013, when President Evo Morales took power in Bolivia. After the death of Chavez, the new Venezuelan President Maduro and Bolivian President Morales tried to continue the same previous cooperation during the Chavez era, but the internal conditions in both countries prevented this. Venezuela suffered from an economic crisis and protests from the opposition, and Bolivia also suffered from protests that led to the resignation of Morales in 2019, and supporters of the United States policy, which is considered the number one enemy of Venezuela, took power. In accordance with the wishes of the Americans, the new Bolivian government severed diplomatic relations with Venezuela. These relations were not restored until after the victory of the Bolivian Union for Socialism party in the 2020 elections.